Repair of Ruptured Abdominal Aortic Aneurysm after Cardiac Arrest: a Case Report - Branco Ribeiro, S (2021)
The management of abdominal aortic aneurysms, especially ruptured abdominal aortic aneurysms, continues to challenge vascular surgeons. A ruptured abdominal aortic aneurysm is associated with a high mortality rate. If cardiopulmonary resuscitation is required before surgical repair, mortality rates are said to be even higher. However, cardiac arrest in patients with ruptured abdominal aortic aneurysm does not accurately predict a nonsalvageable state or preclude functional survival. In these cases, agressive management may be the only hope for survival, and cardiac arrest should not as such contraindicate repair. The objective of this study is to present a successful case of repair of ruptured abdominal aortic aneurysm after cardiac arrest.